WORKSHOP AND TRAINING ON THE USE OF CHATGPT IN THE LEARNING PROCESS AT SENIOR HIGH SCHOOL NAHDLATUL ULAMA PALEMBANG - Akhmad Sayuti; Muhammad Ridho Ardiansyah; Anggoro Aryo Pramuditho; Mahmud; Hasan Pratama Putra; Sabiah Apriyana (Politeknik Kebangsaan, 2025)
The development of artificial intelligence (AI) technology has opened up new opportunities in the world of education, especially in supporting a more interactive and effective learning process. One of the AI technologies that is currently widely used is ChatGPT, a generative language model that can be used to help teachers and students understand material, answer questions, and compile assignments and teaching materials. However, the use of this technology at the Senior High School (SMA) and Vocational High School (SMK) levels, especially in Information Technology subjects, is still very limited. This community service activity aims to provide training on the use of ChatGPT in the Information Technology learning process in SMA/SMK schools. The methods used include delivering material, demonstrating the use of ChatGPT, and direct practice by teachers and students. The training focused on how ChatGPT can be used to understand basic ICT concepts, help compile simple programs, and as a tool in digital learning. The results of this activity showed an increase in participants' understanding and skills in utilizing ChatGPT productively and ethically in learning. In addition, this training also encourages the creation of more innovative and adaptive learning to technological developments. Thus, this training is expected to be the first step in integrating artificial intelligence into the education curriculum, especially in the field of Information Technology.